Administration of mesenchymal stromal cells before renal ischemia/reperfusion attenuates kidney injury and may modulate renal lipid metabolism in rats - Erpicum, Pauline (Sci Rep, 2017)
Mesenchymal stromal cells (MSC) have been demonstrated to attenuate renal ischemia/reperfusion (I/R) damage in rodent models. The mechanisms of such nephro-protection remain largely unknown. Furthermore, the optimal timing of MSC administration has been poorly investigated. Here, we compare the impact of MSC injection 7 days before (MSCD − 7) versus 1 day after (MSCD + 1) renal I/R in rats. Control groups received equivalent volumes of saline at similar time-points (SD − 7 and SD + 1). Right nephrectomy was performed, and left renal ischemia lasted 45 min. After 48-hour reperfusion, we observed significantly improved renal function parameters, reduced apoptotic index and neutrophil/macrophage infiltration in kidney parenchyma, and lower expression of tubular damage markers and pro-inflammatory cytokines in MSCD − 7 in comparison to MSCD + 1 and saline control groups. Next, comparative high-throughput RNA sequencing of MSCD − 7 vs. SD − 7 non-ischemic right kidneys highlighted significant down-regulation of fatty acid biosynthesis and up-regulation of PPAR-α pathway. Such a preferential regulation towards lipid catabolism was associated with decreased levels of lipid peroxidation products, i.e. malondialdehyde and 4-hydroxy-2-nonenal, in MSCD − 7 versus SD − 7 ischemic kidneys. Our findings suggest that MSC pretreatment may exert protective effects against renal I/R by modulating lipid metabolism in rats.